2019
DOI: 10.1111/hae.13875
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated biologics in haemophilia treatment: Current understanding of their long‐term safety

Abstract: PEGylation has proven to be a valuable tool to prolong the half-life of proteins in drug delivery. Covalent binding of one or more polyethylene glycol (PEG) molecules-either with the attachment of small (5-10 kDa) PEG groups, or site-directed attachment of large (≤60 kDa) PEG molecules via linkers-increases the hydrodynamic radius of a protein, improving drug stability and reducing clearance receptor interaction. 1,2 At least 12 PEGylated biopharmaceuticals have been approved in Europe and the United States, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…However, PEG levels in these five patients remained stable over the duration of the extension phase. These plasma PEG measurements are in line with predictions based on simulations of preclinical data 11 . No PEG‐related safety concerns (ie PEG‐related AEs, anti‐PEG antibodies, neurological findings [as performed by the investigator] or renal abnormalities) were reported in the extension.…”
Section: Discussionsupporting
confidence: 80%
“…However, PEG levels in these five patients remained stable over the duration of the extension phase. These plasma PEG measurements are in line with predictions based on simulations of preclinical data 11 . No PEG‐related safety concerns (ie PEG‐related AEs, anti‐PEG antibodies, neurological findings [as performed by the investigator] or renal abnormalities) were reported in the extension.…”
Section: Discussionsupporting
confidence: 80%
“…Properties of the conjugated PEG are known to be driving factors that influence the PK properties of PEGylated proteins [33]. Both the size of the PEG molecule and the type of conjugation are thought to play a role, and it is hypothesized that the differences in these features employed in damoctocog alfa pegol and rurioctocog alfa pegol could contribute to the superior PK profile of damoctocog alfa pegol observed in the current study.…”
Section: Discussionmentioning
confidence: 80%
“…26 No long-term PEG-related safety concerns have been reported in patients after chronic treatment with other PEGylated proteins, including nonacog beta pegol and certolizumab pegol. 29 Long-term exposure data with BAY 94-9027 over 5 years has been reassuring, and more long-term data will soon be available from the PROTECT VIII Kids extension study. Hypersensitivity reactions associated with other FVIII products are uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive review of safety data for PEGylated therapies showed no specific association between particular AEs and PEG exposure over a period of decades 26 . No long‐term PEG‐related safety concerns have been reported in patients after chronic treatment with other PEGylated proteins, including nonacog beta pegol and certolizumab pegol 29 . Long‐term exposure data with BAY 94‐9027 over 5 years has been reassuring, and more long‐term data will soon be available from the PROTECT VIII Kids extension study.…”
Section: Discussionmentioning
confidence: 99%